2015
DOI: 10.1103/physrevb.91.041406
|View full text |Cite
|
Sign up to set email alerts
|

Disorder and screening in decoupled graphene on a metallic substrate

Abstract: Graphene on a dielectric substrate exhibits spatial doping inhomogeneities, forming electronhole puddles. Understanding and controlling the latter is of crucial importance for unraveling many of graphene's fundamental properties at the Dirac point. Here we show the coexistence and correlation of charge puddles and topographic ripples in graphene decoupled from the metallic substrate it was grown on. The analysis of interferences of Dirac fermion-like electrons yields a linear dispersion relation, indicating th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 29 publications
(11 reference statements)
2
36
0
Order By: Relevance
“…It has been theoretically studied and experimentally confirmed that close to the Dirac point, as a consequence of disorder, the carrier density landscape is extremely inhomogeneous and electron-hole puddles form [4][5][6][7][8][9]. Classically, the low-field Hall coefficient in the presence of both electrons and holes is given by…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been theoretically studied and experimentally confirmed that close to the Dirac point, as a consequence of disorder, the carrier density landscape is extremely inhomogeneous and electron-hole puddles form [4][5][6][7][8][9]. Classically, the low-field Hall coefficient in the presence of both electrons and holes is given by…”
Section: Resultsmentioning
confidence: 99%
“…(4) and (5), as shown in the figure (dashed lines), where the disorder potential strength s and the mobility ratio μ e /μ h are extracted from the fitting. ∼30 STM/STS [9] can be made based on the theory [4] assuming that the electronic potential energy of disordered graphene follows Gaussian statistics, which give the probability of finding the local potential within a range dV about V ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A random potential, arising in real graphene samples due to charged impurities and corrugations, manifests itself in formation of electron-hole puddles [4,18,[21][22][23] and qualitatively changes graphene physics at low carrier densities near CNP. Disorder has been proposed as a source of the observed nonvanishing compressibility and quantum capacitance of graphene at CNP [8,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%